Similar effect of running on visual and auditory time perception in the ranges of milliseconds and seconds - Petrizzo, Irene; Chelli, Eleonora; Bartolini, Tommaso; Arrighi, Roberto; Anobile, Giovanni (Frontiers in Psychology, 2023)
The ability to accurately encode events’ duration is of critical importance for almost all everyday activities, yet numerous factors have been reported to robustly distort time perception. One of these is physical activity (i.e. running, walking) but, partly due to the variety of methodologies employed, a full comprehension of the role of exercise on the encoding of time has still to be achieved. Here we tackle the issue with a multifaceted approach by measuring the effect of vigorous running with a time generalization task for visual and auditory stimuli in the range of milliseconds (0.2-0.8 secs) as well as seconds (1-4 secs). At baseline, participants performed both the encoding and decoding at rest while in the experimental conditions the decoding was performed while running. Our results indicate that physical activity in both duration ranges (sub-second and seconds) was expanded during running regardless of the sensory modality used to present the stimuli. Despite this generalized effect of running on perceived duration, we found evidence for the existence of independent timing mechanisms: 1) the perceptual biases induced by running in the two temporal regimes were uncorrelated, 2) sensory precision levels (Weber fraction) were higher for stimuli in the seconds range, 3) sensory precision levels were higher for auditory than for visual stimuli, but only within the sub-second range. Overall, our results support previous findings suggesting (at least partially) separate timing mechanisms for short/long durations and for visual and auditory stimuli. However, they also indicate that physical activity affects all these temporal modules, suggesting a generalized interaction – via generalized and shared resources – between the motor system and the brain time mechanisms.